Meningkatkan Etika Bersosial Media Melalui Bimbingan Klasikal Teknik Brainstorming Siswa Kelas XI MIPA 3 - Suryati, Hamamah Sri; Rispatiningsih, Dwi Maryani; Sujiono, Sujiono; Sudarto, Sudarto; Purnomo, Danang Try; Shadikah, Arina Afiyati; Harto, Sugik (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
The aim of this research is to improve social media ethics by using classical guidance on brainstorming techniques for class XI MIPA 3 students at SMA Negeri 1 Ampel. This research is classroom action research. The subjects of this research were class XI MIPA 3 students with a total of 36 students. This research consists of three cycles with data collection techniques in this research using observation techniques. The data analysis technique used is qualitative descriptive analysis. The research results show that there has been an increase in social media ethics through classical guidance services using brainstorming techniques. In cycle I, there was an increase from pre-cycle 45.7% to 50% in cycle I and experienced another increase in cycle II of 60% and in cycle III to 81.25%. So, with classical guidance services, brainstorming techniques can improve social media ethics in class XI MIPA 3 students at SMA Negeri 1 Ampel Semester 2 for the 2021/2022 academic year.